Knowledge production in the field of professional and technological education in the context of Toyotism (Research, Society and Development, 2020)
Education is a social complex that maintains a relationship of dependence and autonomy with work. In the context of industrialization when Toyotism occurred, the world of work was already being deeply affected by Taylorism and Fordism, with the exploitation of labor by capital, as repetitive, fragmented forms of work were expanded and child labor was included. , etc; the forms of formal work and artisanal work were reduced. As a new way of producing material wealth, it required a new way of producing knowledge. Thus, this work aimed to understand how the knowledge production process takes place in the field of professional and technological education based on toyotism. This research had a qualitative character of the bibliographic type, is based on the works of Marx (1982), Kuenzer (2011), Lukács (2012), among others. We highlight as results: the understanding of the knowledge production process in the field of professional and technological education in the context of Toyotism, enabling its relationship of dependence and autonomy with education. Also, it made it possible to apprehend education as a social complex that maintains dependence and autonomy with work and the models propagated by the industrial revolution toyotism as a new way of producing material wealth and knowledge.